2010
DOI: 10.1007/s00381-009-1069-2
|View full text |Cite
|
Sign up to set email alerts
|

Vagal nerve stimulation for drug-resistant epilepsies in different age, aetiology and duration

Abstract: The best responder could be a young lesional epileptic patient; after 3 years of follow-up, the percentage of responders is still in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 31 publications
4
57
1
2
Order By: Relevance
“…Sixteen Class III studies were identified regarding the efficacy of VNS for seizure treatment in children (see table e-1 for study details). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This group of studies included 2 reports of patients with tuberous sclerosis 16,17 and one report of patients with Dravet syndrome. 18 Ten of 16 studies included subjects through age 18 18 One study of 11 patients with tuberous sclerosis had a mean age of 14, and the range of ages included was 2-35, with 2 subjects older than 19 (27 and 35).…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…Sixteen Class III studies were identified regarding the efficacy of VNS for seizure treatment in children (see table e-1 for study details). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This group of studies included 2 reports of patients with tuberous sclerosis 16,17 and one report of patients with Dravet syndrome. 18 Ten of 16 studies included subjects through age 18 18 One study of 11 patients with tuberous sclerosis had a mean age of 14, and the range of ages included was 2-35, with 2 subjects older than 19 (27 and 35).…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…Sixteen Class III studies were identified regarding the efficacy of VNS for seizure treatment in children (see table e-1 for study details). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This group of studies included 2 reports of patients with tuberous sclerosis 16,17 and one report of patients with Dravet syndrome. 18 Ten of 16 studies included subjects through age 18 One study of 11 patients with tuberous sclerosis had a mean age of 14, and the range of ages included was 2-35, with 2 subjects older than 19 (27 and 35).…”
mentioning
confidence: 99%
“…In the pooled analysis of 481 children, the responder rate was 55% (95% confidence interval [CI] 51%-59%), but there was significant heterogeneity in the data. Two of the 16 studies 11,13 were not included in the analysis because either they did not provide information about responder rate or they included a significant number (.20%) of adults in their population. The pooled seizure freedom rate was 7% (95% CI 5%-10%).…”
mentioning
confidence: 99%
“…However, unblinded trials suggest that VNS is effective in multifocal epilepsy: for example, there was a 75% seizure reduction after 3 years in one trial of adults and pediatric patients. 4 Unblinded studies also support the use of VNS in epilepsy from causes such as Lennox-Gastaut syndrome, tuberous sclerosis, postinfections, and others. 25 The data from the RNS system and DBS of the ANT are still developing, and as of yet the results have not addressed these alternative etiologies directly.…”
Section: Choice Of Therapymentioning
confidence: 93%